Enhancing teacher training skills by strengthening the teaching practice component. Issue 3 (12th March 2018) - Phillips, Heather Nadia; Chetty, Rajendra
Abstract : Purpose: The ongoing theory vs practice debate reinforces the problems facing teacher training institutions which need to challenge traditional programmes and work towards a tighter coherence between coursework and practical experience. Working more closely with schools to restructure teaching practice is necessary in order to create better tuition experience for students. The paper aims to discuss these issues. Design/methodology/approach: This project is situated within an interpretivist paradigm and is qualitative in nature. A sample of four South African education faculties was included. Semi-structured and focus group interviews were used to collect data from fourth-year BEd students, lecturers and in-service practitioners. Findings: The findings indicated that the participants believed that the lack of actual classroom experience, and ineffective organisation of teaching practice, resulted in students feeling ill-equipped. Suggestions are made to improve the organisation of teaching experience and mentorship programmes. Originality/value: This is an original research paper and it has value for teacher education.